Johnson & Johnsons recall headaches : facing familiar challenges in a new era - Fonseca, Mariana (SAGE Knowledge. Cases., 2017)
On September 16, 2010, amidst a congressional inquiry into numerous product recalls over the past 15 months, Johnson & Johnsons Chairman of the Consumer Group, Colleen Goggins, announced her retirement. With the bulk of the recall focused on their flagship product, Tylenol, the tendency was to compare these with the famous recall in 1982, which cemented the publics trust in the company. Unfortunately, that trust has eroded because of their reaction to the numerous current product issues. When it was revealed that subcontractors had secretly bought back Motrin off the shelves without notifying the public that something was wrong with it, J&J found itself with a much larger issue than just public dismay. This phantom recall had compelled FDA regulators to call upon its crime unit to investigate whether or not these actions by Johnson & Johnson constitute criminal behavior.